2015
DOI: 10.1016/j.electstud.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Responsive elections: The effect of public opinion on political campaigns

Abstract: Abstract:Political campaigns exist so that electoral candidates and parties can pursue votes, but what explains their content? It is clear that a lot of thought (and a lot more money) go into election campaigns, but the issues political actors focus on and those that they avoid are not well understood. In this paper we consider the responsiveness of the 2009 German Federal election campaigns to public priorities expressed through the "most important problem" survey question. Through the use of time series mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If the candidate doesn't have a benefit from the economic situation, make an issue that can be associated with the party or candidate and get it Bevan and Krewel 2015). Political campaigns are carried out to win elections and positions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the candidate doesn't have a benefit from the economic situation, make an issue that can be associated with the party or candidate and get it Bevan and Krewel 2015). Political campaigns are carried out to win elections and positions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…A responsive campaign for the public will be able to encourage the public to give support for the campaign. (Bevan & Krewel, 2015). Ganjar was aware that one of the programs that were expected to be positive turned out to be a program that reduced the potential number of votes that he might get.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Future research should study whether electoral vulnerability of different coalition partners influences their responsiveness differently and whether the vulnerability effect varies across the election cycle, such as in the campaign (Bevan and Krewel, 2015). The German case showed that government attention responds when vulnerability comes from outside the government.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These notions of punctuated equilibrium and progressive institutional friction have served as the springboard for an ever-evolving empirical research agenda. Besides input-output analysis connecting public preferences and public spending (Soroka and Wlezien 2005), virtually all intervening aspects of the general linkage process have been examined in a piecemeal manner for various variable pairs gauging the effect of public opinion on agendas venues such as political campaigns (Bevan and Krewel 2015) or executive speeches (Jennings and John 2009). The comparative testing of the friction hypothesis has yielded results that support this pattern (Baumgartner et al 2009; Green-Pedersen and Walgrave 2014).…”
Section: Theorymentioning
confidence: 99%